2020
DOI: 10.3389/fpsyt.2020.00654
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cortical Thickness in the Right Caudal Middle Frontal Is Associated With Symptom Severity in Betel Quid-Dependent Chewers

Abstract: Background: Findings from brain structural imaging studies on betel quid dependence have supported relations between betel quid chewing and alterations in gray matter volume and white matter integrity. However, the effect of betel quid chewing on cortical thickness and the link between cortical thickness and symptom severity remains unascertained. Methods: In this observational study, we compared cortical thickness measures from 24 male betel quid-dependent chewers with 27 male healthy controls. Using FreeSufe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
(125 reference statements)
1
4
0
Order By: Relevance
“…As a result, we contend that the decreased PerAF of the precuneus in BQD chewers may be related to appetite cues and visuospatial processing. Similar to our findings, a recent structural imaging study found a significant decrease in cortical thickness in the precuneus of BQD individuals, which could be related to neurodegeneration caused by chronic BQ chewing ( 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…As a result, we contend that the decreased PerAF of the precuneus in BQD chewers may be related to appetite cues and visuospatial processing. Similar to our findings, a recent structural imaging study found a significant decrease in cortical thickness in the precuneus of BQD individuals, which could be related to neurodegeneration caused by chronic BQ chewing ( 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…The study by Murphy et al [12] revealed that socio-cultural reasons were important for BQ chewers. Reported factors related to reasons for BQ chewing include lower education level [13], longer duration of BQ chewing [13], more chews per day [14]., shorter choice reaction time [15], negative mood [13], working group [16], rural residence [16], BQ users as close friends [16], and a positive attitude toward BQ chewing [16].…”
Section: Introductionmentioning
confidence: 99%
“…People with BQ use often neglect oral hygiene due to unhealthy dental care habits and negative attitudes toward oral health [10]. Studies show that, compared to non-users, BQ users have increased periodontal inflammatory conditions such as bleeding, high plaque index, and gingivitis [11,12], BQ users often experience emotional distress, such as anxiety [13], depression [13], and distress related to betel quid dependence (BQD), such as tolerance, cravings, substance-seeking behavior, and withdrawal symptoms [14][15][16]. These problems may threaten health behaviors related to personal hygiene, health promotion, and overall well-being.…”
Section: Introductionmentioning
confidence: 99%